A novel green enzymatic synthetic route of 2, 3-dihydroxybenzoic acid from glucose and CO2 fixation. (July 2020) - Chen, Kaixun; Fan, Yan; Cao, Xupeng; Liu, Jian; Tian, Hao; Tian, Jing
Graphical abstract: The contrivable tandem enzymatic reaction was consisted of three reaction steps. Step 1(oxidation reaction) was catalyzed by GOD, aimed to oxidize O2 produce H2 O2 . Yield of step 1 was nearly 100 %. The H2 O2 was substrate of step 2(hydroxylation reaction), which oxidize phenol to catechol. The yield of step 2 was 8.2 %, the conversion until end of step 2 was 7.9 %. The reaction system of all previous reaction step was pH 5.0 phosphate buffer. Then, transfer the mixture to reaction still for carboxylation reaction. The reaction step 3(carboxylation reaction) required 0.2 MPa CO2, catalyzed by 2, 3-DHBD in 2.7 M potassium bicarbonate solution. The yield of step 3 was 29.3 %, total conversion was 2.4 %. Highlights: Application of 2, 3-dihydroxybenzoic acid decarboxylase in a green synthetic route. Green synthesis of 2, 3-dihydroxybenzoic acid from CO2, glucose and phenol. 2, 3-dihydroxybenzoic acid decarboxylase was robust under the oxidation stress. Directed hydroxylation is the bottleneck to this green enzymatic reaction. Abstract: The enzymatic carbon fixation is a promising approach to deal with greenhouse gas emission and is usually accompanied with energy consumption during the reduction of CO2 . As a very important route, the carboxylation can convert CO2 to organic carbon without extra requirement of reduction power and is hoped as a greener solution, especially for some non-bulk chemicals, such as medical intermediates. Here, a concept-proof trail of green enzymatic process of conversing both of CO2 and benzene to produce 2, 3-dihydroxybenzoic acid (2, 3-DHBA), which is the intermediate for fine chemicals, is introduced with O2 from air and glucose. The results showed that the conversion catechol by 2, 3-dihydroxybenzoic acid decarboxylase (2, 3-DHBD) alone was around 30 %, with an overall conversion from phenol of 2.4 %, which was limited by the in-situ production of catechol. This trail contributed a green enzymatic route for the production of 2, 3-DHBA.